For one more day - Albom, Mitch, 1958- (Hyperion, 2006)
After years of drinking, being rejected by his wife and daughter, and a suicide attempt, ex-baseball star Charley Benetto returns to his childhood home where he encounters the ghost of his mother, who tells him family secrets and guides him in making his life better.